Model Arrhenius untuk Pendugaan Laju Respirasi Brokoli Terolah Minimal - Nurul Imamah; Rokhani Hasbullah; Lilik Pujantoro Eko Nugroho (PERTETA, 2016)
AbstractMinimally processed broccoli are perishable product because it still has some metabolism process duringthe storage period. One of the metabolism process is respiration. Respiration rate is varied depend on the commodity and storage temperature. The purpose of this research are: to review the respiration pattern of minimally processed broccoli during storage period, to study the effect of storage temperature to respiration rate, and to review the correlation between respiration rate and temperature based on Arrhenius model. Broccoli from farming organization “Agro Segar” was processed minimally and then measure the respiration rate. Closed system method is used to measure O2 and CO2 concentration. Minimally processed broccoli is stored at a temperature of 0oC, 5oC, 10oC and 15oC. The experimental design used was completely randomized design of the factors to analyze the rate of respiration. The result shows that broccoli is a climacteric vegetable. It is indicated by the increasing of O2 consumption and CO2 production during senescence phase. The respiration rate increase as high as the increasing of temperature storage. Models Arrhenius can describe correlation between respirationrate and temperature with R2= 0.953-0.947. The constant value of activation energy (Eai) and pre-exponential factor (Roi) from Arrhenius model can be used to predict the respiration rate of minimally processed broccoli in every storage temperatureAbstrakBrokoli terolah minimal merupakan produk yang mudah rusak (perishable). Hal tersebut terjadi karena jaringan tumbuhan masih melakukan kegiatan metabolisme selama penyimpanan. Salah satu proses metabolisme yang terjadi adalah respirasi. Besarnya laju respirasi bervariasi tergantung jenis komoditi dan sangat dipengaruhi oleh suhu penyimpanan. Penelitian ini bertujuan mengkaji pola respirasi brokoli terolah minimal selama penyimpanan, mengkaji pengaruh suhu terhadap laju respirasi dan menganalisis hubungan laju respirasi dengan suhu penyimpanan berdasarkan model Arrhenius. Brokoli yang diperoleh dari kelompok tani “Agro Segar” diolah secara minimal untuk kemudian diukur laju respirasinya. Metode sistem tertutup digunakan untuk mengukur konsentrasi O2 dan CO2. Brokoli terolah minimal disimpan pada suhu 0oC, 5oC, 10oC, dan 15oC. Rancangan percobaan yang digunakan adalah rancangan acak lengkap dengan 4 taraf perlakuan. Hasil penelitian menunjukan brokoli merupakan jenis sayuran klimaterik yang ditandai dengan adanya peningkatan konsumsi O2 dan produksi CO2 pada fase pelayuan. Laju respirasi meningkat seiring dengan meningkatnya suhu penyimpanan. Hubungan laju respirasi dengan suhu penyimpanan terbukti dapat dijelaskan menggunakan model Arrhenius yang memiliki nilai R2 = 0.953-0.947. Nilai konstanta energi aktivasi (Eai) dan faktor preeksponensial (Roi) dari model Arrhenius dapat digunakan untuk memprediksi laju respirasi brokoli terolah minimal pada setiap suhu penyimpanan.